An observational study of driver distraction in England. - Sullman, Mark J. M. (Elsevier Science B.V., Amsterdam., 2012)
This study set out to investigate the proportion of UK drivers who engage in some form of distracting behaviour whilst driving. Data were collected by roadside observation in six urban centres in the South of England. The observations took place on randomly selected roads at three different time periods during two consecutive Tuesdays. The data revealed that 14.4% of the 7168 drivers observed were found to be engaged in a distracting activity. The most frequently observed distraction was talking to a passenger, followed by smoking and using a mobile phone. Younger drivers were signiﬁcantly more likely to be distracted in general and by talking to passengers, while older drivers were less likely to be distracted by adjusting controls or using a mobile phone.
Keywords: Driver distraction Distraction Cell phone Mobile phone Crash risk Observation